Effect of Co-Curricular Activities on Academic Performance of Pupils in Buyanja Sub-County Rukungiri District. - Kyobutungi, Brendah (Kabale University, 2025)
The study aimed to examine the impact of co-curricular activities on academic performance among pupils in Buyanja Sub-County, Rukungiri District, with specific objectives to identify the challenges hindering their effective implementation, determine their effect on pupils' academic performance, and assess the perceived benefits. A cross-sectional design utilizing a mixed methods approach was employed to gather both quantitative and qualitative data from 75 respondents, including teachers and headteachers. The findings revealed that inadequate funding (73.33%) and insufficient infrastructure (66.67%) are the most significant challenges hindering the implementation of co-curricular activities. Additionally, 60% of respondents identified a lack of trained personnel as a critical issue, while 26.67% noted a lack of interest from pupils as a concern. Despite these challenges, 66.67% of teachers reported that co-curricular activities positively impact academic performance by enhancing time management skills, reducing stress, and fostering greater engagement in studies, while 13.33% perceived a negative impact, and 20% saw no significant effect. Furthermore, these activities offer numerous benefits, with 80% of respondents highlighting enhanced social skills, 73.33% noting improved academic performance, 66.67% recognizing better physical health, and 60% identifying increased self-esteem. The study concludes that while co-curricular activities significantly contribute to the academic and overall development of pupils, addressing the identified challenges is crucial for maximizing their impact. Recommendations include increased funding, training for teachers, and better infrastructure to support co-curricular programs in primary schools within Buyanja Sub-County. Additionally, further research should be conducted to investigate the impact of having trained personnel on the quality and effectiveness of co-curricular activities, as well as to explore how adequate funding influences the sustainability and outcomes of these activities.